Preparation and Comparison of Simple Tax Avoidance Scores Based on Profitability Ratio in Banking Companies in the LQ45 Index - Bi Rirantri; Eni Srihastuti; Moch Wahyudi (LP2M IAIN Palopo, 2026)
This study aims to develop and implement a simple tax avoidance score based on the Effective Tax Rate (ETR) and illustrate its relationship to profitability ratios in banking companies listed in the LQ45 Index for the 2020-2024 period. The study uses a descriptive and comparative quantitative approach using financial statement data. The results show that banks with relatively high profitability tend to have high and stable tax avoidance scores. The simple ETR-based score is effective for mapping tax avoidance patterns based on company profitability performance.